A surface modified La0.6Sr0.4Co0.2Fe0.8O3-δ ultrathin membrane for highly efficient oxygen separation - He, Beibei; Zhang, K.; Ling, Y.; Xu, J.; Zhao, L. (Elsevier BV, 2014)
A surface modified La0.6Sr0.4Co0.2Fe0.8O3−δ sandwich ceramic membrane with ultrathin dense layer, 4 μm, has been developed for highly efficient oxygen separation. Compared with conventional dense disks, the new structure significantly increases oxygen permeation flux by a magnitude. This impregnated sandwich structure offers the highest performance of oxygen separation up to now due to the reduced thin dense layer and enhanced surface exchange kinetics.